Social patterning of telephone health-advice for diarrhoea and vomiting: analysis of 24 million telehealth calls in England - Adams, NL; Rose, TC; Elliot, AJ; Smith, G; Morbey, R; Loveridge, P; Lewis, J; Studdard, G; Violato, M; O'Brien, SJ; Whitehead, M; Taylor-Robinson, DC; et al. (Elsevier, 2018)
Objectives Gastrointestinal (GI) infections are common and most people do not see a physician. There is conflicting evidence of the impact of socioeconomic status (SES) on risk of GI infections. We assessed the relationship between SES and GI calls to two National Health Service (NHS) telephone advice services in England. Methods Over 24 million calls to NHS Direct (2010–13) and NHS 111 (2013–15) were extracted from Public Health England (PHE) syndromic surveillance systems. The relationship between SES and GI calls was assessed using generalised linear models (GLM). Results Adjusting for rurality and age-sex interactions, in NHS Direct, children in disadvantaged areas were at lower risk of GI calls; in NHS 111 there was a higher risk of GI calls in disadvantaged areas for all ages (0–4 years RR 1.27, 95% CI 1.25–1.29; 5–9 years RR 1.43, 95% CI 1.36–1.51; 10–14 years RR 1.36, 95% CI 1.26–1.41; 15–19 years RR 1.59, 95% CI 1.52–1.67; 20–59 years RR 1.50, 95% CI 1.47–1.53, 60 years and over RR 1.12, 95% CI 1.09–1.14). Conclusions Disadvantaged areas had higher risk of GI calls in NHS 111. This may relate to differences in exposure or vulnerability to GI infections, or propensity to call about GI infections.